THE MAIN FACTORS AND CHARACTERISTICS OF THE DEVELOPMENT OF SEASONAL RECREATION SYSTEMS IN THE REPUBLIC OF UZBEKISTAN - Hamdamov Eldorbek (Scholars Digest Publishing, 2023)
This article talks about the phenomenon of seasonality and the natural, social and economic factors that affect it in tourism and recreation activities. Seasonal recreational activity is considered a widespread type of activity nowadays, and it is mainly a type of social activity.
Keywords: Tourism, seasonal tourism, seasonal periods, «dead» season, two-season regions, regional recreation systems, one-season regions, non-seasonal regions.